2012
DOI: 10.1097/brs.0b013e318237aae4
|View full text |Cite
|
Sign up to set email alerts
|

The Study on Comparison of 3 Techniques for Transarticular Screw Placement in the Lower Cervical Spine

Abstract: There is a high risk of injury to the anterior branch of the cervical nerve roots and vertebral artery if the screws were too long, and the Takayasu technique was used. However, the rate of facet splitting is high if the Dalcanto technique was applied. Klekamp's technique is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Another supplemental posterior instrumentation technique that involves a more minimally invasive approach uses screws placed across the facet joints ("transfacet screws"). This method has been advocated as an alternative to lateral mass screw/rod fixation in the cervical spine 2,3,11,20 and pedicle screw fixation in the lumbar spine. 1,21 Transfacet screws have an inherent mechanical advantage over lateral mass trajectories in that they obtain purchase in 4 cortices, and it has been reported that transfacet screws provide greater pullout strength than cervical lateral mass fixation.…”
mentioning
confidence: 99%
“…Another supplemental posterior instrumentation technique that involves a more minimally invasive approach uses screws placed across the facet joints ("transfacet screws"). This method has been advocated as an alternative to lateral mass screw/rod fixation in the cervical spine 2,3,11,20 and pedicle screw fixation in the lumbar spine. 1,21 Transfacet screws have an inherent mechanical advantage over lateral mass trajectories in that they obtain purchase in 4 cortices, and it has been reported that transfacet screws provide greater pullout strength than cervical lateral mass fixation.…”
mentioning
confidence: 99%
“…A further comparison showed superiority of the Klekamp technique in terms of neurovascular risks and facet fractures. 19 Using an entry point similar to the one we used in the present study, Klekamp et al 7 entered the superior lateral mass 1 mm medial and 1 mm inferior to the center, whereas DalCanto et al 2 entered 2 mm caudal to the center of the lateral mass.…”
Section: Discussionmentioning
confidence: 89%
“…While a more minimally invasive approach using screws placed across the facet joints (i.e. TFS) is not as widely used as LMSR, it can be quite a useful procedure for isolated facet joint fusion and has been advocated as an alternative to LMSR in the cervical spine [ 22 , 33 , 34 ]. Klekamp et al [ 19 ] were the first to note that TFS placement provided comparable, if not greater, pullout resistance than LMSR placement in the cervical spine, with the possible explanation that TFS penetrated upper and lower articular processes with four layers of cortical bone altogether, while LMS penetrated mostly through cancellous bone.…”
Section: Discussionmentioning
confidence: 99%